TINDAK PIDANA PERAMBAHAN KAWASAN HUTAN PRODUKSI TERBATAS OLEH MASYARAKAT DI WILAYAH DESA BUNGKU KECAMATAN BAJUBANG KABUPATEN BATANG HARI - Suhaimi Hamid (Jurnal LEX SPECIALIS, 2014)
Forests in Indonesia are known to have Biodiversity Very High, but the forests of Indonesia Resources Turns Very Fast And worsens From year to year, singer caused illegal logging practices,  forest fires and encroachment And Peladang That move.  According to PT data. Ecosystem Restoration Indonesia (PT. REKI) Reached More Than 16,000 Hectares Of The 101.355 hectare land being restored OR restored to review so natural forests Back. Operating aggressive encroachers The land has to change their power unilaterally to review Operates Illegal logging and  Also planted with oil palm crops. Many diagnostic factors affecting the Land Conflicts BETWEEN lying on Economic, Social, Ecology And Needs agricultural land. Forms of Land Conflicts BETWEEN lay overlapping Stewardship and land ownership disputes. On the other parties, social conflicts can be occurred BETWEEN THE original inhabitants immigrant population, as for Yang discussed hearts Singer problem is conflict BETWEEN PT. Ecosystem Restoration Indonesia (PT. REKI) WITH society. Things That Which led Government Barriers hearts Keywords : Crime of Encroachment Limited Production Forest